Compact Broadband Circularly Polarized Metasurface Antenna with Split-Annular Slot Ground Structure - Nathapat Supreeyatitikul; Nonchanutt Chudpooti; Chuwong Phongcharoenpanich (My University, 2023)
This paper presents a broadband CP MTS-inspired antenna with split-annular slot ground structure. The CP radiation and antenna configuration are deployed characteristic mode analysis (CMA). The proposed CP MTS-inspired antenna with split-annular slot ground structure comprised of upper substrate and lower substrate. The upper substrate consisted of $5\times 5$ uniformly MTS unit cells, and the split-annular slot ground plane and microstrip feed line are included on the lower substrate. In CMA results, the $5\times 5$ MTS-inspired unit cells generated CP radiation by Modes 1 and 2. Besides, the split-annular slot ground structure can be produced two orthogonal electric fields at the center frequency of 5 GHz by Modes 3 and 5 for excitation source. This proposed antenna achieved simulated IBW of 59.4% (3.57 - 6.55 GHz), and simulated ARBW of 24.22% (4.43 - 5.64 GHz). The maximum gain at 4.7 GHz is 5.72 dBic, which has RHCP characteristic radiation. The proposed antenna is appropriate functionally for C-band wireless applications.
Keywords: Antenna Design and Analysis; Advanced Antenna and Metasurface Technologies; Energy Harvesting in Wireless Networks